Rural firms, farms and the local economy - a focus on small and medium-sized towns - Paul Courtney; Denis Lépicier; Bertrand Schmitt (European Regional Science Association (ERSA), 2005)
Small and medium-sized towns have traditionally formed an integral part of the agricultural sector and wider rural economy, acting as a source of farm inputs, a first destination of farm outputs and as a source of consumer goods and services to farm households. In recent years, this relationship has been substantially eroded through processes socio-economic restructuring, including the transformation of agriculture and a decline in other primary industries. Further, a number of endogenous and exogenous drivers have resulted in the uneven development of rural economies throughout Europe, leading not only to disparities but also to decline of small and medium sized towns as thriving economic and service centres. As a result, these settlements have received increasing attention from policy makers aiming to both maintain the traditional socio-economic fabric of rural areas, and to stimulate rural development through territorial, as opposed to sectoral – and namely agricultural – approaches. This paper considers these two issues through an analysis of local economic linkages in and around small and medium-sized towns. Using primary data collected in a study of thirty towns across five European countries, the paper examines the degree to which local firms and farms are integrated into the local economies of such towns relative to other sectors, and identifies the organisational characteristics associated with strong and weak local integration. The implications of the findings are discussed in the context of evolving European rural development policy.
Keywords: 330